Increase throughput of CCM security mode using MKP - Ahmad Zulkarnain, Zuriati (Scientific Research Publishing, 2014)
A security protocol is used to ensure the messages transferred over a network free from attack. The CCM security operation mode adopts CTR, and CBC-MAC schemes to implement message ciphering and authentication respectively. There are two limitations of CCM including the secret key which should refresh for each 264 blocks in CTR mode and the authentication operation of CBC-MAC works in sequential fashion on multi-processor system. In this paper, we have proved that the Multiple Key Protocol (MKP) can be used within CTR mode to increase the size of the transferred message. Also, we have showed that the DMAC algorithm is able to decrease the time of authentication operation on multi-processing units system.